2015
DOI: 10.7717/peerj.1155
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of female physical attractiveness to body fatness

Abstract: Aspects of the female body may be attractive because they signal evolutionary fitness. Greater body fatness might reflect greater potential to survive famines, but individuals carrying larger fat stores may have poor health and lower fertility in non-famine conditions. A mathematical statistical model using epidemiological data linking fatness to fitness traits, predicted a peaked relationship between fatness and attractiveness (maximum at body mass index (BMI) = 22.8 to 24.8 depending on ethnicity and assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 88 publications
(166 reference statements)
3
29
0
Order By: Relevance
“…Some reports of elevated rates of miscarriage and caesarean sections among anorexic women exist, as do reports of similar negative reproductive outcomes among obese women . Although tentative, Wang and colleagues estimate optimal BMI among Caucasian women to be approximately 23, combining the effects of BMI on all‐cause mortality and future potential fertility based on BMI at age 20. This estimate further supports epidemiological data, demonstrating that BMI extremes negatively impact fitness and fertility.…”
Section: Gene Pleiotropy Natural Selection and Obesitymentioning
confidence: 99%
“…Some reports of elevated rates of miscarriage and caesarean sections among anorexic women exist, as do reports of similar negative reproductive outcomes among obese women . Although tentative, Wang and colleagues estimate optimal BMI among Caucasian women to be approximately 23, combining the effects of BMI on all‐cause mortality and future potential fertility based on BMI at age 20. This estimate further supports epidemiological data, demonstrating that BMI extremes negatively impact fitness and fertility.…”
Section: Gene Pleiotropy Natural Selection and Obesitymentioning
confidence: 99%
“…Surprisingly, in a recent epidemiological study of ten populations from diverse African, Asian and Caucasian backgrounds, an inverse correlation between body fatness or BMI and subjective perception of physical attractiveness was uncovered [39]. As adipose tissue is mostly perceived as unattractive and harmful, and even indicative of an intemperate and unhealthy lifestyle, it has received little scientific attention until some decades ago, when it was identified as a vital organ in vertebrate physiology [31], [32], [40].…”
Section: Sex-specific Differences In Adipose Tissue Distribution Pattmentioning
confidence: 99%
“…The sample size was based on the protocol of an international study, which included participants from urban areas in 10 countries with sample sizes ranging from 53 to 260 per country. 10 From this international study, the results showed consistent relationships between study countries, irrespective of sample size, indicating that the sample size per country was large enough for the research question. The sample selection was stratified by gender and village ward.…”
Section: Sample Size Selectionmentioning
confidence: 58%
“…Following the protocol of the main study, the rankings were then converted to scores in the range 1-9 using the following equation: Score = 1 + (ranking −1) *0.4, with rankings ranging from 1 to 21. 10 The known level of %BF of each image (X-axis) was plotted against the median attractiveness ranking (Y-axis) for the total group and the subgroups separately. Regression lines were fitted and the R 2 of the regression equation was presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation